2022
DOI: 10.1021/acs.analchem.2c01421
|View full text |Cite
|
Sign up to set email alerts
|

A Drop-in, Focus-Extending Phase Mask Simplifies Microscopic and Microfluidic Imaging Systems for Cost-Effective Point-of-Care Diagnostics

Abstract: Microscopic imaging and imaging flow cytometry have wide potential in point-of-care assays; however, their narrow depth of focus necessitates precise mechanical or fluidic focus control of a sample in order to acquire high-quality images that can be used for downstream analysis, increasing the cost and complexity of the imaging system. This complexity represents a barrier to miniaturization and translation of point-of-care assays based on microscopic imaging or imaging flow cytometry. To address this challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The high-speed images are processed and analyzed to extract information about cell size and deformability. Meng et al introduced a focus-extending phase mask that can extend the depth of focus by at least 5-fold for high-quality image acquisition in microfluidic imaging systems . The phase mask eliminates the need for frequent refocusing between samples, extends the field-of-view for low-cost objectives, and enables flow cytometry without flow focusing.…”
Section: Sensor and Detection Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The high-speed images are processed and analyzed to extract information about cell size and deformability. Meng et al introduced a focus-extending phase mask that can extend the depth of focus by at least 5-fold for high-quality image acquisition in microfluidic imaging systems . The phase mask eliminates the need for frequent refocusing between samples, extends the field-of-view for low-cost objectives, and enables flow cytometry without flow focusing.…”
Section: Sensor and Detection Technologymentioning
confidence: 99%
“…Meng et al introduced a focus-extending phase mask that can extend the depth of focus by at least 5-fold for high-quality image acquisition in microfluidic imaging systems. 85 The phase mask eliminates the need for frequent refocusing between samples, extends the field-of-view for lowcost objectives, and enables flow cytometry without flow focusing. Mandracchia et al reported optofluidic scanning microscopy for super-resolution, live cell imaging.…”
Section: ■ Sensor and Detection Technologymentioning
confidence: 99%
“…The DoF defines the depth range of an object that can be sharply imaged by a given optical imaging system, and is determined by the operating wavelength, effective focal length and aperture size of the imaging lens. In many biomedical imaging applications, such as in cytometry 1 , 2 , histology 3 , and endoscopy 4 6 , high-resolution imaging over a large spatial scale is often desired; for instance, a pathological examination is typically performed with a high numerical-aperture ( ) objective to visualize cellular and subcellular features of tissue specimens, but it is accompanied by limited field-of-view (FoV) and DoF. Therefore, to image large-area pathological/cytology slides, either objects or imaging optics should be scanned and refocused repetitively, which is costly and labor-intensive.…”
Section: Introductionmentioning
confidence: 99%